CONSTRAINTS FACING GIRLS’ SECONDARY EDUCATION IN SOKOTO STATE - Giwa, Alh. A.B.; Abdulmalik, Idris (Sokoto Educational Review, 2020)
This paper discussed the major constraints facing girls’ secondary education in Sokoto State. These are non-compliance with the philosophy of Nigerian education, religious/cultural disposition of the people, government policy, financial problems and parental bias. The paper proved that the philosophy of Nigerian education was not complied with. The paper also proved that Islam emphasizes equality in education for both sexes. However, the paper confirmed that majority of the people in the state favour early marriage of girls and the preference of boy’s education to girl’s education. At the end, recommendations were proffered to reduce or remove the constraints.